You don't see the world through the same eyes any more: The impact of sexual offending work on police staff. (December 2019) - Parkes, Ruth; Graham-Kevan, Nicola; Bryce, Jo
This paper examines the experiences of police staff in England who work with sexual offence material (SOM). Eleven officers completed a questionnaire then took part in semi-structured interviews. The data were analysed in two stages: Interpretative Phenomenological Analysis was used to illuminate the 'lived experience' of participants, and establish a theme structure. Clinical models of workplace trauma were then employed to explore the theme 'Impact of working with sexual offending'. Impact includes cognitive intrusions and increased suspiciousness. The authors identify where officers' accounts intersect with nascent symptoms of both Vicarious Traumatisation (McCann and Pearlman, 1990) and post-traumatic stress disorder (PTSD).